PENGARUH REGULASI EMOSI DALAM AKTIVITAS OLAHRAGA FISIK TERHADAP PERILAKU SELF-HARM - Mutiara Hartika Budiman; Salwa Aulia Putri; Rashiqa Putri Prabakti; Iqlima Shaffiani Al-Abror; Firly Alfiana Rahmawati; Rama Wijaya Abdul Rozak (Cahaya Ilmu Bangsa Institute, 2025)
Self-harm is often interpreted as a form of self-injury, this behavior experiences very intense difficulties and difficulty in regulating negative emotions caused by negative thoughts that always blame oneself. This research aims to see the influence of emotional regulation in physical sports activities on self-harm behavior. This research uses qualitative methods. Data collection techniques using two main methods, interviews and observation, were used to collect data in this research. This research was conducted by 4 participants, 1 teenager and 3 early adults, 3 subjects were interviewed without intervention and 1 subject underwent intervention. The results of this research are that exercise has a significant relationship with reducing the desire to do self-harm. Physical activity can reduce stress and anxiety which often trigger self-harm behavior. The subject also admitted that the results of the intervention made the subject feel more confident and increased self-control which helped the individual overcome the negative impulses that emerged. As long as the body does exercise, it is known that the body will release endorphins, thereby increasing mood and creating a feeling of calm. Engagement in a regular exercise routine can divert attention from thoughts or feelings that trigger destructive behavior, thereby making exercise an effective way to manage emotions, improve mental well-being, and reduce the tendency to self-harm.